1990
DOI: 10.1128/mcb.10.9.5011
|View full text |Cite
|
Sign up to set email alerts
|

Functional state of the epidermal growth factor-receptor complexes during their internalization in A-431 cells.

Abstract: Functional state of internalized epidermal growth factor (EGF) receptor in A431 cells has been studied. The use of photoaffinity [12"I]EGF derivative allowed us to establish that inside the cell the EGF retains its connection with the receptor. With the help of polyclonal antibodies to phosphotyrosine, it has been shown that EGF-receptor complexes maintain their phosphorylated state during internalization. The internalized EGF receptor kinase as well as that localized in the plasma membrane appeared to be able… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In addition to the colocalization of molecules with microspheres, the disposition of the plasma membrane around the microspheres constitutes an important analytical parameter. Upon stimulation by growth factor, activated EGF receptors rapidly internalize (19, 20). Thus, for EGF‐coated microspheres, the microsphere internalization provides important evidence that signaling proceeds in the same or very similar manner as with the soluble ligand.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the colocalization of molecules with microspheres, the disposition of the plasma membrane around the microspheres constitutes an important analytical parameter. Upon stimulation by growth factor, activated EGF receptors rapidly internalize (19, 20). Thus, for EGF‐coated microspheres, the microsphere internalization provides important evidence that signaling proceeds in the same or very similar manner as with the soluble ligand.…”
Section: Resultsmentioning
confidence: 99%
“…Several lines of evidence suggest that signals can be generated by endosomal receptors and that these receptors may be important for persistent signaling processes (Baass et al, 1995;Carpenter, 2000). Thus, despite the fact that the acidic pH of endosomes might be expected to cause ligand-receptor dissociation and deactivation of the receptor, it has been demonstrated that EGF-receptor complexes remain intact, dimerized, and phosphorylated during early stages of endocytosis (Cohen and Fava, 1985;Lai et al, 1989;Nesterov et al, 1990;Sorkin and Carpenter, 1991). Furthermore, the association of EGFR with effector proteins was demonstrated in endosomal fractions from rat liver (Di Gugliemo et al, 1994) and mammary cells (Burke et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This has also been shown for another growth factor receptor, colony stimulating factor 1 (Carlberg et al, 1991). The EGF receptor kinase is known to be active in the multivesicular body, as EGF stimulation causes a prolonged phosphorylation of the receptor (Nesterov et al, 1990), and it has been shown to be more highly phosphorylated in endosomes than at the plasma membrane (Wada et al, 1992). In multivesicular bodies incubated with [γ-32 P]ATP the two major proteins that are phosphorylated are annexin I and the receptor itself.…”
Section: Annexin Imentioning
confidence: 81%